Personality modulates amygdala and insula connectivity during humor appreciation: An event-related fMRI study. (2nd November 2018) - Berger, Philipp; Bitsch, Florian; Nagels, Arne; Straube, Benjamin; Falkenberg, Irina
ABSTRACT: Previous research and theory implicate that personality traits, such as extraversion and neuroticism, influence the processing of humor, as indicated by alterations in the activation of fronto-temporal and mesocorticolimbic brain regions during humor processing. In the current study, we sought to complement these findings by testing whether inter-individual differences in functional connectivity of humor-related brain regions are modulated by stable personality characteristics during humor processing. Using fMRI techniques, we studied 19 healthy subjects during the processing of standardized humorous and neutral cartoons. In order to isolate the specific effects of humor appreciation, subjective funniness ratings, collected during the scanning procedure, were implemented in the analysis as parametric modulation. Two distinct clusters in the right amygdala and the left insula were identified. Seed-to-voxel connectivity analysis investigating the effects of personality on inter-individual differences in functional connectivity revealed that amygdala and insula connectivity with brain areas previously related to humor comprehension (e.g. middle temporal gyrus) and appreciation (e.g. caudate nucleus) were significantly modulated by personality dimensions. These results underscore the sensitivity of humor processing to moderating influences, such as personality, and call attention to the importance of brain connectivity measures for the investigation of inter-individual differences in the processing of humor.